A Novel Pathway Regulates Thyroid Hormone Availability in Rat and Human Hypothalamic Neurosecretory Neurons - Kalló, Imre; Mohácsik, Petra; Vida, Barbara; Zeöld, Anikó; Bardóczi, Zsuzsanna; Zavacki, Ann Marie; Farkas, Erzsébet; Kádár, Andrea; Hrabovszky, Erik; Arrojo e Drigo, Rafael; Dong, Liping; Barna, László; et al. (PLOS ONE, 2012)
Hypothalamic neurosecretory systems are fundamental regulatory circuits influenced by thyroid hormone. Monocarboxylate-transporter-8 (MCT8)-mediated uptake of thyroid hormone followed by type 3 deiodinase (D3)-catalyzed inactivation represent limiting regulatory factors of neuronal T3 availability. In the present study we addressed the localization and subcellular distribution of D3 and MCT8 in neurosecretory neurons and addressed D3 function in their axons. Intense D3-immunoreactivity was observed in axon varicosities in the external zone of the rat median eminence and the neurohaemal zone of the human infundibulum containing axon terminals of hypophysiotropic parvocellular neurons. Immuno-electronmicroscopy localized D3 to dense-core vesicles in hypophysiotropic axon varicosities. N-STORM-superresolution-microscopy detected the active center containing C-terminus of D3 at the outer surface of these organelles. Double-labeling immunofluorescent confocal microscopy revealed that D3 is present in the majority of GnRH, CRH and GHRH axons but only in a minority of TRH axons, while absent from somatostatin-containing neurons. Bimolecular-Fluorescence-Complementation identified D3 homodimers, a prerequisite for D3 activity, in processes of GT1-7 cells. Furthermore, T3-inducible D3 catalytic activity was detected in the rat median eminence. Triple-labeling immunofluorescence and immuno-electronmicroscopy revealed the presence of MCT8 on the surface of the vast majority of all types of hypophysiotropic terminals. The presence of MCT8 was also demonstrated on the axon terminals in the neurohaemal zone of the human infundibulum. The unexpected role of hypophysiotropic axons in fine-tuned regulation of T3 availability in these cells via MCT8-mediated transport and D3-catalyzed inactivation may represent a novel regulatory core mechanism for metabolism, growth, stress and reproduction in rodents and humans.